PENGARUH MODAL KERJA DAN PENJUALAN TERHADAP LABA BERSIH PADA PT. AKR CORPORINDO Tbk YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) PERIODE 2010-2020 - Cindy Aulia Lorenza; Sucipto, Sucipto; Kurniawan, Bambang (Program Studi Manajemen Keuangan Syariah, 2024)
The purpose of the study is to know the effect of working capital and sales on net profit at PT AKR CORPORINDO TBK listed in the JAKARTA ISLAMIC INDEX (JII) This research is included in a descriptive quantitative research with PT. AKR CORPORINDO Tbk as a population, the sampling technique is to use purposive sampling, the data collection technique is an online questionnaire. Based on the results of data management, partial working capital is obtained affecting the net profit of PT. AKR CORPORINDO TBK with a significant value of (2,635> 1,682), while partially sales affect the net profit of PT. AKR CORPORINDO TBK with significant value (2,573> 1,682). Then, the results showed that simultaneously the variables of working capital and sales affected the net profit of PT. AKR CORPORINDO with a significant value of 7,086> 3,230. Keywords : Effect of working capital, sales on net profit